Penerapan Fintech Sebagai Platform Modal Kerja Bagi Pengrajin Bakul Purun di Banjarbaru - Ali Sadikin; Dahniar Dahniar; Fahmi Roy Dalimunthe; Muhammad Yudi Rachman; Lily Permata Sari (Jurnal Pengabdian ILUNG (Inovasi Lahan Basah Unggul), 2022)
Many UKM in Indonesia are experiencing problems in their business. There are also problems faced by UKM including very small business capital, not applying digital marketing to their products until products are monotonous (less attractive). What's more, during the current covid-19 pandemic, sluggish economic conditions, UKM Bakul Purun "Aresa" Banjarbaru have difficulty selling their products, because they only use traditional marketing, besides that, very minimal business capital also hampers production which ultimately reduces production. their income. To overcome the problems above, a strategic and comprehensive step is needed, namely by applying digital marketing sales such as Whatapps business, Instagram, etc. The problem of small business capital in UKM Aresa , can be overcome by using Fintech lending such as the Lumbung Dana application. The output obtained from the service at UKM Aresa is from a technical aspect, there is an increase in sales of basket purun products because they have used e-commerce (digital marketing) so that their market share and market share increases, which in turn increases the income and profits of these UKM. In the non-technical aspect, the output is that UKM there can already use fintech applications such as Lumbung Dana, if in the past the business capital was only around 1-3 million, now it's around 5-8 million. Increased business capital will affect the amount of production of purun baskets and their derivative products, ultimately affecting income and profits of around 6%-10% for UKM Aresa in particular and the community of bakul purun craftsmen there in general. Key words: Fintech Lending, Lumbung dana